CERITA RAKYAT SENTANI: KASUARI DAN BURUNG PIPIT (Analisis Struktural Menurut Sistem Kode Roland Barthes) - Siswanto NFN (Balai Bahasa Provinsi Papua, 2019)
The folktale of Kasuari dan Burung Pipit is well-known in Sentani, Papua. As a valuable literature for Sentani people, it is necessary to study and analyze the message of the folktale. This is a qualitative research applying the descriptive method. The analysis uses a message transaction modus based on the theory of the semiotics of Roland Bhartes. The data of this research is the story of Kasuari dan Burung Pipit. The data was submitted by observation (through recordings and note-taking) and interviews. The result shows, based on the analysis, that the message transaction modus of the story includes 1) the proairetic code; 2) the heurmeuneutic code; 3) the code of semes or signifiers; 4) the symbolic code; and 5) the culture code.